The Emerging Functions of LRRK2 and Rab GTPases in the Endolysosomal System - Kuwahara, Tomoki; Iwatsubo, Takeshi (Frontiers in Neuroscience, 2020)
The leucine-rich repeat kinase 2 (LRRK2), the most common causative gene for autosomal-dominant familial Parkinson’s disease, encodes a large protein kinase harboring multiple characteristic domains. LRRK2 phosphorylates a set of Rab GTPases in cells, which is enhanced by the Parkinson-associated LRRK2 mutations. Accumulating evidence suggests that LRRK2 regulates intracellular vesicle trafficking and organelle maintenance including Golgi, endosomes and lysosomes. Furthermore, genetic knockout or inhibition of LRRK2 cause lysosomal abnormalities in rodents and primates, and cells from Parkinson’s patients with LRRK2 mutations also exhibit altered lysosome morphology. Cell biological studies on LRRK2 in a diverse cellular context further strengthen the potential connection between LRRK2 and regulation of the endolysosomal system, part of which is mediated by Rab phosphorylation by LRRK2. We will focus on the latest advances on the role of LRRK2 and Rab in relation to the endolysosomal system, and discuss the possible link to the pathomechanism of Parkinson’s disease.